Optimizing Productive Waqf: Driving the Growth of Small and Medium Enterprises in Padang - Widad Rifai, Ahmad (Takaza Innovatix Labs Ltd., 2025)
This research investigates the effectiveness of productive waqf as a funding mechanism for the development of Small and Medium Enterprises (SMEs) in Padang. Utilizing qualitative methodologies, including in-depth interviews with waqf managers and SME owners, the study highlights the potential of productive waqf to provide sustainable financial resources while fostering community support and social responsibility. Findings reveal that productive waqf not only alleviates financial barriers for SMEs but also promotes economic empowerment and resilience within the local community. However, the study identifies several challenges, including a lack of awareness among entrepreneurs and regulatory inconsistencies, which hinder the effective implementation of productive waqf. To maximize its impact, this research recommends enhancing outreach and educational initiatives to improve understanding of waqf mechanisms, establishing a robust regulatory framework to ensure transparency and accountability, and providing targeted training for waqf managers. Additionally, the study calls for policymakers to implement supportive measures that streamline processes and incentivize SME participation in waqf programs. Overall, productive waqf holds substantial promise for driving economic growth and development in Padang, contributing significantly to the sustainability of SMEs in the region.